Analisis Kebijakan Anti-Bullying dalam Konteks Pendidikan Islam : Implikasi untuk Lingkungan Sekolah - Refa Choirur Rizki; Dwi Nur Anjani; Kamila Rahma Shalehah; Ma’wah Salsabila (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2024)
This study discusses the anti-bullying policy in the context of Islamic education at SMAN 107 Jakarta, with the aim of describing the implementation of the policy and its application to the relationship between students and between students and teachers and the school community. The method used is a mixed method, which combines qualitative and quantitative approaches to obtain comprehensive data. The study found that bullying, both verbal and non-verbal, has a serious impact on students’ mental and physical health, as well as creating an unconducive school environment. The anti-bullying policy implemented in these schools is based on government regulations and Islamic values, which emphasize the importance of maintaining human dignity and creating a safe learning environment. The implications of this study show that Islamic education can play an important role in shaping students’ character and preventing bullying in schools.